2022
DOI: 10.1002/adhm.202101605
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Luminescence Photography of a Swellable Hydrogel Dressing with a Traffic‐Light Response to Oxygen

Abstract: Sensor-integrated wound dressings are emerging tools applicable to a wide variety of medical applications from emergency triage to at-home monitoring. Uncomfortable, unnecessary wound dressing changes may be avoided by providing quantitative insight into tissue characteristics related to wound healing such as tissue oxygenation, pH, and exudate/transudate volume. Here, a simple cost-effective methodology for quantifying oxygen and pH in a swellable hydrogel dressing using a single photograph is presented. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The porphyrin–fluorescein conjugate displayed a red dominant (Pt-porphyrin) emission at low oxygen level and a green dominant (fluorescein) emission in room air, resulting in red-to-green traffic-light response. Reprinted with permission from ref . Copyright 2022 Wiley-VCH GmbH.…”
Section: Peripherally Functionalized Porphyrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…The porphyrin–fluorescein conjugate displayed a red dominant (Pt-porphyrin) emission at low oxygen level and a green dominant (fluorescein) emission in room air, resulting in red-to-green traffic-light response. Reprinted with permission from ref . Copyright 2022 Wiley-VCH GmbH.…”
Section: Peripherally Functionalized Porphyrinsmentioning
confidence: 99%
“…Results from an in vivo tourniquet porcine model showed that the device is sensitive toward the oxygen partial pressure range of 0–80 mmHg and exhibited a reproducible response to changes in intramuscular oxygen. The same group further developed a swellable hydrogel dressing which displayed traffic-light response to oxygen . Hydrogels are characterized by their analogy to extracellular matrix owing to their soft and porous skeleton together with their huge water holding capacity and biocompatibility.…”
Section: Peripherally Functionalized Porphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic polymers mainly include polyethylene glycol (PEG), polydopamine (PDA), polyacrylamide (PAM), polyvinyl alcohol (PVA), etc. [57][58][59][60] Due to the controllable molecular weight and physical and chemical properties, synthetic polymer hydrogels have unique advantages in skin tissue engineering. Compared with natural polymers, synthetic polymers exhibit higher mechanical strength and controllable biodegradation rate.…”
Section: Synthetic Polymer-based Hydrogelsmentioning
confidence: 99%
“…This sensing mechanism has gained traction in a variety of fields and has proven to be applicable for both in vitro studies of cell metabolism and in vivo applications for physiological monitoring with implantable or wearable transcutaneous devices. While transcutaneous devices for physiological O 2 monitoring have made significant progress in recent years, [11][12][13][14][15] this perspective will mainly focus on the in vitro use of luminescent sensors that are quenched by O 2 with the main goal of guiding the reader towards a logical sensor choice for their desired application. As such, we are not attempting to review the entire field of O 2 sensing for metabolic evaluation, but rather to provide the reader with examples of what is possible to help guide their research and facilitate innovation in this domain.…”
mentioning
confidence: 99%